1988
DOI: 10.1192/bjp.152.1.34
|View full text |Cite
|
Sign up to set email alerts
|

Growth Hormone Response to Clonidine After Recovery in Patients with Endogenous Depression

Abstract: The growth hormone response to clonidine was measured in ten drug-free recovered patients, seven of whom had previously been tested when endogenously depressed, and compared with the response in ten individually matched controls. In eight of the patients there was an impairment of the growth hormone response, despite clinical recovery, although the hypotensive effect of clonidine in these patients was normal. This is suggestive of a persisting abnormal alpha2-adrenoceptor function in forebrain regions after re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

1991
1991
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…Clonidine induces endogenous GHRH release by a mechanism dependant on alpha 2 agonism (Ghigo et al 1990) and the original finding, of an attenuated GH response to clonidine in depression (Matussek et al 1980), has been replicated many times. However, many studies using clonidine to investigate noradrenergic function in depression have not measured HPA function (Checkley et al 1981;Lesch et al 1987b;Ansseau et al 1988;Mitchell et al 1988;Thomas et al 1989;Coplan et al 1995;Gann et al 1995). Those which have, have generally found a negative correlation between basal measures of plasma or urinary cortisol and GH release in response to monoamine challenge with clonidine (Matussek et al 1980;Dolan and Calloway 1986;Amsterdam and Maislin 1990), which could be explained by an effect of cortisol on pituitary GH release, without any change in hypothalamic noradrenergic activity.…”
Section: Discussionmentioning
confidence: 92%
“…Clonidine induces endogenous GHRH release by a mechanism dependant on alpha 2 agonism (Ghigo et al 1990) and the original finding, of an attenuated GH response to clonidine in depression (Matussek et al 1980), has been replicated many times. However, many studies using clonidine to investigate noradrenergic function in depression have not measured HPA function (Checkley et al 1981;Lesch et al 1987b;Ansseau et al 1988;Mitchell et al 1988;Thomas et al 1989;Coplan et al 1995;Gann et al 1995). Those which have, have generally found a negative correlation between basal measures of plasma or urinary cortisol and GH release in response to monoamine challenge with clonidine (Matussek et al 1980;Dolan and Calloway 1986;Amsterdam and Maislin 1990), which could be explained by an effect of cortisol on pituitary GH release, without any change in hypothalamic noradrenergic activity.…”
Section: Discussionmentioning
confidence: 92%
“…Indeed, there are many short-term changes in the noradrenergic and dopaminergic neurotransmissions implying that both noradrenergic and dopaminergic activities during the challenges may not be comparable to the day when the MMN was recorded. However, several lines of evidence have shown that the clonidine test may represent a stable trait and a single assessment seems to be sufficient for investigating central noradrenergic activity (Mitchell et al, 1988;Trestman et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Several investigators have documented a blunted growth hormone response after clonidine challenge. [27][28][29] Cortisol responses to methamphetamine and desipramine challenges also suggest dysfunction of the NE system. The bulk of the evidence suggests that metabolite changes play little or no role in the pathophysiology of depression.…”
Section: Role Of Ne In Depressionmentioning
confidence: 99%